The potential for mitochondrial therapeutics in the treatment of primary open-angle glaucoma: a review - Kuang, Grace; Halimitabrizi, Mina; Edziah, Amy-Ann; Salowe, Rebecca; O’Brien, Joan M. (Frontiers in Physiology, 2023)
Glaucoma, an age-related neurodegenerative disease, is characterized by the death of retinal ganglion cells (RGCs) and the corresponding loss of visual fields. This disease is the leading cause of irreversible blindness worldwide, making early diagnosis and effective treatment paramount. The pathophysiology of primary open-angle glaucoma (POAG), the most common form of the disease, remains poorly understood. Current available treatments, which target elevated intraocular pressure (IOP), are not effective at slowing disease progression in approximately 30% of patients. There is a great need to identify and study treatment options that target other disease mechanisms and aid in neuroprotection for POAG. Increasingly, the role of mitochondrial injury in the development of POAG has become an emphasized area of research interest. Disruption in the function of mitochondria has been linked to problems with neurodevelopment and systemic diseases. Recent studies have shown an association between RGC death and damage to the cells' mitochondria. In particular, oxidative stress and disrupted oxidative phosphorylation dynamics have been linked to increased susceptibility of RGC mitochondria to secondary mechanical injury. Several mitochondriatargeted treatments for POAG have been suggested, including physical exercise, diet and nutrition, antioxidant supplementation, stem cell therapy, hypoxia exposure, gene therapy, mitochondrial transplantation, and light therapy. Studies have shown that mitochondrial therapeutics may have the potential to slow the progression of POAG by protecting against mitochondrial decline associated with age, genetic susceptibility, and other pathology. Further, these therapeutics may potentially target already present neuronal damage and symptom manifestations. In this review, the authors outline potential mitochondria-targeted treatment strategies and discuss their utility for use in POAG.